Ethnobotany of the Batek tribe in Kuala Koh, Kelantan, Malaysia - Mat Esa, Muhamad Ikhwanuddin (2019)
Plants and environment play important roles in Batek tribe culture. They possess a high level of knowledge related to forests due to unique intimacy with the forests and their heavy dependents on forests produce for their livelihood. The indigenous knowledge among Batek tribe is inherited from generation to generation through verbal communication from the eldest, but none of this knowledge has been considered, neither has it been documented systematically. Deforestation in the nearby area caused the resources of medicinal plants that were once abundant depleted tremendously. Due to this urgent call, therefore the objective of this study is to document the traditional uses of various indigenous plants, which are commonly used among Batek tribe, to determine the most frequently used species by measuring the relative importance of each species and identify the level of homogeneity among information gathered within the Batek community, to identify the plant part, modes of preparation and ways of administration used for medication of each medicinal plant. In this study, an ethnobotanical survey was conducted using semi-structured questionnaire method to obtain information on the use of medicinal plants for traditional healthcare among Batek people in Kuala Koh, Gua Musang Territory, Kelantan.Then, the literature searches were carried out for the evaluation on the current status of investigations on these plants. This study has recorded 50 species belonging to 36 families of medicinal plants used by the Batek tribe. Spatholobus ferrugineus (Zoll. & Moritzi) Benth, Eurycoma longifolia Jack and Marantodes pumilum (Blume) Kuntze had the highest RFC. Leaves were the most frequently used plant’s part (42%). Fifty percent of medications are prepared as decoctions, and mostly administered orally. This study provides the first ethnobotanical study on medicinal plants used among Batek tribe in Kuala Koh. Future studies towards conserving the reported species and standardizing traditional herbal medicine administration are recommended.